The Ideation of Environmental Sustainability: Evidence from Phuket, Thailand - FUCHS, Kevin (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.v12.5(53).07, 2021)
The fundamental people-to-people nature of tourism makes it more vulnerable than other industries and adds more difficulties in adapting to the pandemic. The mass tourist destination Phuket has suffered economic consequences due to a decline in international passenger arrivals, with inadequate domestic tourism to take their place. It is reasonable to state that, in some way, the absence of tourism will impact Phuket’s status quo of environmental sustainability. Environmental sustainability is a primary theme in the contemporary tourism and hospitality industry. Environmentally sustainable consumer behavior and ecotourism are important aspects of environmental protection, which eventually benefits society. This paper presents evidence related to the current state of environmental sustainability based on an ongoing work-in-progress research project. The study is led by the ethnographic principles of qualitative data collection. Moreover, the empirical data for this study were gathered through non-participant observations, unstructured interviews with local stakeholders, and the collecting of a variety of materials. The study discloses indecisive results based on the good practices that were observed, as well as behavior and outcomes that contradict the philosophy of environmental sustainability. The results of this paper have practical implications for residents, visitors, and policymakers and offer the scientific community a starting point for advanced research about environmental sustainability in the mass tourism destination Phuket, Thailand.